2018
DOI: 10.1016/j.bpj.2017.11.3687
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Promotes Cytolysin a Activity by Stabilizing the Intermediates during Pore Formation

Abstract: Biological processes performed by proteins interacting with and processing DNA and RNA are key to cell metabolism and life. Detailed insights into these processes provide essential information for understanding the molecular basis of life and the pathological conditions that develop when such processes go awry. The next scientific breakthrough consists in the actual, direct, real-time observations and measurements of the individual mechanisms involved, in order to validate and complete the current biological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…For characterizing proteins, while ClyA nanopores were advantageous compared to β -barrel pores such as AHL because of their larger pore lumen, ClyA pores were also more unstable, necessitating directed evolution to produce mutants that could form more stable nanopores (Soskine et al, 2013). This is consistent with oligomeric α -helical protein assemblies such as the ClyA pore being less stable than β -PFT pores (Gouaux, 1998; Woolfson et al, 2012), especially because their membrane-inserted α helices are significantly stabilized by surrounding lipids and cholesterol (Sathyanarayana et al, 2018; Tanaka et al, 2015; Kristan et al, 2009), whereas the rigid β -barrels of β -PFTs are mainly stabilized by inter-strand interactions of the membrane inserted β barrels (Gouaux, 1998). Hence, our study of the inter-protomer interfacial interactions which may either stabilize or destabilize the large α -PFT ClyA pore may yield insights into general factors that could stabilize higher order α -helical assemblies.…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…For characterizing proteins, while ClyA nanopores were advantageous compared to β -barrel pores such as AHL because of their larger pore lumen, ClyA pores were also more unstable, necessitating directed evolution to produce mutants that could form more stable nanopores (Soskine et al, 2013). This is consistent with oligomeric α -helical protein assemblies such as the ClyA pore being less stable than β -PFT pores (Gouaux, 1998; Woolfson et al, 2012), especially because their membrane-inserted α helices are significantly stabilized by surrounding lipids and cholesterol (Sathyanarayana et al, 2018; Tanaka et al, 2015; Kristan et al, 2009), whereas the rigid β -barrels of β -PFTs are mainly stabilized by inter-strand interactions of the membrane inserted β barrels (Gouaux, 1998). Hence, our study of the inter-protomer interfacial interactions which may either stabilize or destabilize the large α -PFT ClyA pore may yield insights into general factors that could stabilize higher order α -helical assemblies.…”
Section: Discussionsupporting
confidence: 57%
“…Our screening protocol illustrates that Y27 present on the membrane inserted α -helix of ClyA ( α A1 in Figure 6 c ) forms a hydrogen bond with A179 present on the membrane-inserted hydrophobic motif, which is in close proximity to the helix α A1. Recent work from our group has shown that the mutation Y27A reduced the lytic activity of ClyA by 24-fold (Sathyanarayana et al, 2018) and the mutation Y27F completely abolished lytic activity. Further, Y27 was associated with a putative cholesterol recognition and consensus motif (CRAC) located on the α helix of ClyA and the neighbouring residues D25 and K29 were associated with strong cholesterol binding sites (Giri Rao et al, 2016; Sathyanarayana et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations